2009
DOI: 10.1155/2009/267107
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Compounds That Inhibit IGF-I Signaling in Hyperglycemia

Abstract: Increased responsiveness of vascular cells to the growth factor IGF-I has been implicated in complications associated with diabetes. Here we describe the development of an assay and screening of a library of compounds for their ability to accelerate cleavage of the transmembrane protein integrin-associated protein (IAP) thereby disrupting the association between IAP and SHPS-1 which we have shown as critical for the enhanced response of vascular cells to IGF-I. The cell-based ELISA utilizes an antibody that sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
(67 reference statements)
1
9
0
Order By: Relevance
“…1C). Both antibodies detected the 50-55 kDa N-glycosylated and >200 kDa proteoglycan isoforms of CD47 and a previously described 36 kDa proteolytic fragment of CD47 (28, 35) in the immunoprecipitates from WT Jurkat cells that were absent in the corresponding immunoprecipitates from JinB8 cells. The CD47 antibody B6H12 detected several nonspecific bands in VEGFR2 immunoprecipitates from JinB8 cells that were not detected by the CD47 antibody R529.…”
Section: Resultsmentioning
confidence: 87%
“…1C). Both antibodies detected the 50-55 kDa N-glycosylated and >200 kDa proteoglycan isoforms of CD47 and a previously described 36 kDa proteolytic fragment of CD47 (28, 35) in the immunoprecipitates from WT Jurkat cells that were absent in the corresponding immunoprecipitates from JinB8 cells. The CD47 antibody B6H12 detected several nonspecific bands in VEGFR2 immunoprecipitates from JinB8 cells that were not detected by the CD47 antibody R529.…”
Section: Resultsmentioning
confidence: 87%
“…Our previous studies have demonstrated that CD47 is released into conditioned medium by Jurkat T cells ( Kaur et al, 2011 ). This could be soluble CD47 produced by proteolytic cleavage of its IgV domain ( Maile et al, 2009 ) or intact CD47 associated with EVs. In order to identify a potential functional role of this released CD47 in T cell activation, we transferred conditioned media (CM) between wild type Jurkat and CD47-deficient JinB8 T cell cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Because CD47 has been shown to be present on platelet ectosomes ( Sadallah et al, 2011 ) and as a proteolytically cleaved fragment in conditioned media ( Maile et al, 2009 ), we considered whether the transfer of CD47 to the CD47-deficient cells restores their sensitivity to modulation of TCR signaling by TSP1. Alternatively, this effect of CD47 could be indirect, and indirect effects of CD47 are obviously necessary to account for the ability of conditioned medium from CD47-deficient cells to confer resistance of WT Jurkat cells to TSP1 inhibition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of diabetes may hasten the development of endothelial lesions and atherosclerosis, which may be minimized by the presence of antioxidants [43, 44]. …”
Section: Discussionmentioning
confidence: 99%